Private Health Insurance in Ireland: Trends and Determinants - Kapur, Kanika (The Economic and Social Review, 2020)
This study examines the determinants of demand for private health insurance in Ireland. Survey data commissioned by the Health Insurance Authority from 2009 to 2017 are used to estimate multivariate models of health insurance demand. The results show that older and sicker individuals are more likely to have private health insurance, suggesting that adverse selection may be an issue in the Irish market. Irish-born are found to be more likely to have private health insurance. Preferences for health insurance also play an important role in predicting the purchase of health insurance. After controlling for the role of socio-economic factors and individual preferences, annual variations in the economy are not found to affect private health insurance coverage.